A Social Contract Account for CSR as an Extended Model of Corporate Governance (I): Rational Bargaining and Justification - Sacconi, Lorenzo (Journal of business ethics, 2006)
This essay seeks to give a contractarian foundation to the concept of Corporate Social Responsibility (CSR), meant as an extended model of corporate governance of the firm. It focuses on justification according to the contractarian point of view (leaving compliance and implementation problems to a related article, [Sacconi 2004b, forthcoming in the Journal of Business Ethics]). It begins by providing a definition of CSR as an extended model of corporate governance, based on the fiduciary duties owed to all the firm’s stakeholders. Then, by establishing the basic context of incompleteness of contracts and abuse of authority, it analyses how the extended view of corporate governance arises directly from criticism of the contemporary neo-institutional economic theory of the firm. Thereafter, an application of the theory of bargaining games is used to deduce the structure of a multi-stakeholder firm, on the basis of the idea of a constitutional contract, which satisfies basic requirements of impartial justification and accordance with intuitions of social justice. This is a sequential model of constitutional bargaining, whereby a constitution is first chosen, and then a post-constitutional coalition game is played. On the basis of the unique solution given to each step in the bargaining model, the quest for a prescriptive theory of governance and strategic management is accomplished, so that I am able to define an objective-function for the firm consistent with the idea of CSR. Finally, a contractarian potential explanation for the emergence of the multi-fiduciary firm is provided.